1992
DOI: 10.1001/archderm.1992.01680120059004
|View full text |Cite
|
Sign up to set email alerts
|

Natural History of Sensitizations in Atopic Dermatitis

Abstract: The detection of food allergy in a child presenting with AD is likely to indicate a prognosis of severe AD and should be considered by dermatologists as a potentially important predictor of further respiratory symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0
1

Year Published

1994
1994
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(38 citation statements)
references
References 36 publications
0
37
0
1
Order By: Relevance
“…Atopy prevalences ranged from 47% to 75% (Table II). [10][11][12][13][14][15][16][17][18][19][20][21] Lower levels of atopy-AD association were seen in cross-sectional population-based studies. Thirteen of 65 surveys were identified, and atopy prevalences ranged from 7% to 78% (Table III).…”
Section: How Atopic Is Ad At the Population Level?mentioning
confidence: 99%
See 1 more Smart Citation
“…Atopy prevalences ranged from 47% to 75% (Table II). [10][11][12][13][14][15][16][17][18][19][20][21] Lower levels of atopy-AD association were seen in cross-sectional population-based studies. Thirteen of 65 surveys were identified, and atopy prevalences ranged from 7% to 78% (Table III).…”
Section: How Atopic Is Ad At the Population Level?mentioning
confidence: 99%
“…Of these, 7 studies concluded that the number of SPTs, IgE-antibody specificities, and/or IgE levels were significantly associated with AD severity (Table IV). [12][13][14]16,22,[32][33][34] How useful is the knowledge of IgE sensitization in discriminating between the phenotype of AD and other skin diseases or persons without skin disease?…”
Section: Is Ige Sensitization a Marker Of Severity In Ad?mentioning
confidence: 99%
“…The overall prevalence of food allergy in infants with AD ranged from 20 to 80% in various studies, and may be estimated at 30%. Guillet found that severe AD and younger age are risk factors for food allergy [12]. Clinical symptoms of patients with food-sensitive AD often improve with an increase in age [13].…”
Section: Prevalence Of Food Allergy In Admentioning
confidence: 99%
“…When it is well known that atopic dermatitis [37][38][39][40][41][42] and food allergy [43][44][45][46][47][48][49] have their onset within the first year of life in 70-100% of infants [37][38][39][40][41][42], and in the second in 69-96% of cases [43,44], it may not be clear that allergy to a panel of foods be gins before the first year of age in a wide proportion of ba bies [45][46][47][48][49]. For example allergy to cow milk evidently begins in at least 72%, and to egg in 71% of infants [45][46][47].…”
Section: Introductionmentioning
confidence: 99%